Numerical simulation study on suppression effect of water mist on PMMA combustion under external radiant heat flux - Zhao, Lanming; Cao, Dongxu; Chen, Yong; Liu, Hanru; You, Tianchi; Li, Caoyue; Zhang, Hongming (Frontiers in Materials, 2023)
Numerical model was built with fire dynamic simulator and theocratical simulation was carried out to investigate the suppression effect of water mist on ignition and combustion process of typical solid material PMMA under external radiant heat flux. Characteristic parameters such as ignition time, surface temperature, heat release rate and temperature distribution of flame central plane during ignition and combustion process under different thermal radiant fluxes were obtained and compared with experimental results. The suppression effect of spray droplets on ignition and combustion process was analyzed and discussed. The results show the theoretical calculations of combustion characteristic parameters are in good agreement with experimental measurements. Water mist droplets can effectively delay the ignition time. Quantitative data proves that the water mist flow rate at 0.9 L/(min·m2) can delay the ignition time of samples by about 1100 s while the radiant heat flux is 50 kW/m2. The simulation results can provide theoretical support and data reference for typical solid material fire prevention and fire extinguishment in practice.